Batu Boraspati dan Batu Kelang, Keterkaitannya dengan Kehidupan Agraris Masyarakat Pakpak - Dyah Hidayati (Berkala Arkeologi Sangkhakala, 2011)
AbstractPakpak community belief that there is spirit have control their land, Beraspati ni Tano. To show their mutual respect to that, they make lizard or flying lizard ornament on their traditional house and also symbolize that with lizard or flying lizard stone statue. At the rice planting season, they run the ritual for plentiful harvest hoping.